THE POLITICS OF LAW CONCERNING THE TENURE OF VILLAGE HEAD REVIEWED FROM THE CONSTITUALISM PERSPECTIVE - Achmad Hariri (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2020)
The politics of law is an instrument of law-making to achieve legal objectives, and the objectives of the law-making must be in line with the constitutional norms. The constitution is a foundation rule for law-making (the politics of law), and in its development, the modern state constitution must be constitutionalism. Constitutionalism is an idea that the constitution must limit the power to hinder the abuse due to unrestricted power. The politics of constitutional law can be seen in the first amendment, namely, Article 7 of the 1945 Constitution: the tenure of a president is five years and limited to two periods, the 1945 constitution is, therefore, constitutionalism. The power limitation of high state institutions is constitutional, but in Law No. 6 of 2014 concerning Villages, some norms are contrary to the constitution: Article 39 related to the tenure of the village head. The tenure of village head in this article is relatively longer than the executive position in supra-village government, that is six years and can be re-elected for three periods, meaning that the village head can occupy the position for a maximum of 18 years. This tenure is eight years longer than the tenure of the president, governor, regent and mayor, thus, it is likely for the village head to conduct the